A pilot study comparing two field tests with the treadmill run test in soccer players - Aziz, A. R.; Tan, F. H. Y.; Teh, K. C. (Journal of Sports Science & Medicine, 2005)
This study compares the performances obtained during soccer-specific field tests of the 20 m multistage shuttle run test (MST) and the Yo-Yo intermittent endurance test (YIET), with the measured maximal oxygen uptake (VO2max) obtained in both field tests as well as that obtained in the traditional test of running to exhaustion on a treadmill (TRT), in young trained soccer players. Twenty-one National-level youth players performed, in random order, the MST and YIET to determine the relationship between the two field tests. From these, eight randomly chosen players performed their field tests as well as a TRT, equipped with an ambulatory gas exchange measurement device. Pearson correlation coefficient analysis showed that the players' performance (i.e. distance covered) in the MST and YIET was correlated (r = 0.65, p < 0.01). Players' performance in the YIET was not significantly correlated with the measured VO2max obtained in the same YIET nor with the measured VO2max obtained in the MST and in the TRT (all p > 0.05). In contrast, significant correlations were observed between the players' performance in the MST with the measured VO2max obtained in the same MST and in the YIET (both p < 0.05); and attained almost statistical significance with the measured VO2max in the TRT (p = 0.06). The lack of association between distances covered in the YIET with all the measured VO2max values suggest that measured VO2max per se may not be suitable to characterize soccer players' intermittent endurance performance. In comparison with the MST, the YIET may be a more favourable field-based assessment of soccer player's endurance performance.